2020
DOI: 10.48550/arxiv.2006.15074
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cleaning the NVD: Comprehensive Quality Assessment, Improvements, and Analyses

Abstract: Vulnerability databases are vital sources of information on emergent software security concerns. Security professionals, from system administrators to developers to researchers, heavily depend on these databases to track vulnerabilities and analyze security trends. How reliable and accurate are these databases though?In this paper, we explore this question with the National Vulnerability Database (NVD), the U.S. government's repository of vulnerability information that arguably serves as the industry standard.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Note that this database has been discontinued since 2016. 6 https://twitter.com 7 https://avast.com/exploit-protection.php. This link was provided by de Sousa et al [41], but it is no longer available.…”
Section: Exploit Likelihoodmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that this database has been discontinued since 2016. 6 https://twitter.com 7 https://avast.com/exploit-protection.php. This link was provided by de Sousa et al [41], but it is no longer available.…”
Section: Exploit Likelihoodmentioning
confidence: 99%
“…For CVSS version 3 [57,58], Chen et al [29,30] and Anwar et al [6] also reported the strong performance of DL-based models (e.g., CNN and graph convolutional neural network [95]). Some other studies did not directly predict severity score from SV descriptions, instead they aggregated the predicted values of the CVSS Exploitability (see section 3) and Impact metrics (see section 4) using the formulas of CVSS version 2 [50,86,171,193], version 3 [50,86,139] and WIVSS [171].…”
Section: Severity Scorementioning
confidence: 99%
See 1 more Smart Citation
“…Jimenez et al [P12] found that only 75% of vulnerability reports had an associated fix. Vulnerability reports are often incomplete and missing references [9].…”
Section: Label Noisementioning
confidence: 99%
“…Unfortunately, SV data preparation is not a trivial task [7]. High-quality SV data is notoriously difficult to obtain due to its natural infrequency [8], inconsistent reporting [9], and the unwillingness of organisations to make their sensitive data public [10]. It is widely recognized that data noise can severely impact the quality of an SVP model and eventually negatively impact the validity of the research outcomes [11], [12].…”
Section: Introductionmentioning
confidence: 99%